2017
DOI: 10.18632/oncotarget.15962
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 regulates reactive oxygen species via NOX4 during chemotherapy-induced senescence

Abstract: Mcl-1, a Bcl-2 family member, is highly expressed in a variety of human cancers and is believed to enhance tumorigenic potential and chemotherapy resistance through the inhibition of apoptosis and senescence. We previously reported that Mcl-1′s regulation of chemotherapy-induced senescence (CIS) is dependent on its ability to prevent reactive oxygen species (ROS) generation. In this report, we demonstrate that Mcl-1-regulated CIS requires not only ROS, but specifically mitochondrial ROS, and that these events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…MCL-1 plays a role in suppressing the generation of reactive oxygen species (ROS). 29 Treatment with MS1/NPs had little, if any, effect on MCL-1 expression and was associated with the upregulation of MUC1-C, NF-κB p65 and BCL2A1 (Fig. 4b ), consistent with the finding that ROS activate the MUC1-C→NF-κB p65 pathway.…”
Section: Resultssupporting
confidence: 82%
“…MCL-1 plays a role in suppressing the generation of reactive oxygen species (ROS). 29 Treatment with MS1/NPs had little, if any, effect on MCL-1 expression and was associated with the upregulation of MUC1-C, NF-κB p65 and BCL2A1 (Fig. 4b ), consistent with the finding that ROS activate the MUC1-C→NF-κB p65 pathway.…”
Section: Resultssupporting
confidence: 82%
“…Bolesta et al 28 have shown that MCL1 localizes to mitochondria and prevents senescence and loss of phosphorylation of retinoblastoma (RB) protein, which is followed by inhibition of ROS production 29 . MCL1 is also involved in the downregulation of p27 expression, a critical inducer of senescence 29 , and decreases ROS production and senescence via NOX4 during chemotherapy 30 . This can be one possibility of downregulation of senescence and ROS in osteoarthritic chondrocytes in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…SGK1 can negatively regulate JNK signaling, an important inducer of superoxide species by modulating complex I activity of the electron transport chain ( 87 , 88 ). In addition, SGK1-mediated inactivation of GSK3-β facilitates MCL1 localization to the mitochondria to significantly reduce mitochondrial ROS production through inhibition of NOX4 expression, adversely affecting the response to chemotherapy ( 88 , 89 ). It is important to note, however, that in models of lung cancer, MCL1 may also promote ROS production from the mitochondria by binding to voltage-dependent anion channels and increasing the mitochondrial flux of calcium ( 90 ).…”
Section: Pi3k/akt Signaling Maintains Redox Balance In Cancer Cellsmentioning
confidence: 99%